2013
DOI: 10.1002/asi.22847
|View full text |Cite
|
Sign up to set email alerts
|

Evolving academic library specialties

Abstract: The purpose of this review is to examine the shaping of librarianship in the academic context through the literature of career specialties, with Abbott's (1988) system of professions providing an analytic framework. The specialties investigated are systems librarian, electronic resource librarian, digital librarian, institutional repository manager, clinical librarian and informationist, digital curator/research data manager, teaching librarian/ information literacy educator, and information and knowledge mana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
78
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(84 citation statements)
references
References 95 publications
2
78
0
4
Order By: Relevance
“…An on-going jurisdictional conflict between these two professions is already known from the literature (e.g. Cox and Corrall, 2013;O'Connor, 2009a;Ray, 2001;Danner, 1998;Van House and Sutton, 1996). In this particular case, the interviews suggested that the Library was indeed keen to extend its jurisdiction into RDM, more so than IT Services.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…An on-going jurisdictional conflict between these two professions is already known from the literature (e.g. Cox and Corrall, 2013;O'Connor, 2009a;Ray, 2001;Danner, 1998;Van House and Sutton, 1996). In this particular case, the interviews suggested that the Library was indeed keen to extend its jurisdiction into RDM, more so than IT Services.…”
Section: Discussionmentioning
confidence: 95%
“…Most notably, this threat comes from Information Technology, digital information (both digitized and born-digital), and the Internet. It is argued that this has led to "a reinvention of the access role" -the core jurisdiction of librarianship for Abbott -potentially in competition with IT professionals because the Library has taken on the management of electronic content (Cox and Corrall, 2013).…”
Section: Libraries and Librariansmentioning
confidence: 99%
See 1 more Smart Citation
“…An Abbottonian perspective (Abbott, 1988) on professional roles sees work as a competitive space where professions compete for "jurisdiction" over different types of work (Cox and Corrall, 2013). It could be argued that librarianship as an internally well-organised profession (for example, with strong professional identity and knowledge networks) has the ability to out-manoeuvre less-organised professions (such as research administration) or smaller professions (particularly archives and records management) however relevant their professional knowledge.…”
Section: Future Library Roles?mentioning
confidence: 99%
“…In recent years this role has become more formalized with the establishment of copyright offices and the increasing number of librarian positions addressing copyright, such as copyright officers, copyright librarians, and scholarly communication librarians (Patterson, 2016, p. 3-4;Graham & Winter, 2016;Kawooya, Veverka, & Lipinski, 2015). Librarians have also taken on an increasing instructional role in relation to information literacy (see for example Julien, Tan, & Merillat, 2013, p. 82;andCox &Corrall, 2013, p. 1534), of which copyright forms a part, and thus education is often a central focus of these new copyright offices and positions.…”
Section: Introductionmentioning
confidence: 99%